2015
DOI: 10.3390/antiox4020345
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of the Content of Phytochemicals in Fresh and Fresh-Cut Vegetables

Abstract: Vegetables and fruits have beneficial properties for human health, because of the presence of phytochemicals, but their concentration can fluctuate throughout the year. A systematic study of the phytochemical content in tomato, eggplant, carrot, broccoli and grape (fresh and fresh-cut) has been performed at different seasons, using liquid chromatography coupled to triple quadrupole mass spectrometry. It was observed that phenolic acids (the predominant group in carrot, eggplant and tomato) were found at higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This behavior was similar in all gas concentrations, with no interaction effect between treatments and storage period. In minimally processed plants, injuries in the plant tissue caused by cutting the fruits and/or vegetables lead to an increase of respiratory rate and ethylene production, causing a stimulus to the formation of secondary metabolites, which are produced as a plant defense mechanism (ALARCÓN-FLORES et al, 2015;KLUGE et al, 2006), and may increase the functional food value. In addition, the biosynthesis of phenolic compounds may continue after harvest and increase during storage at low temperatures (CONCELLÓN et al, 2007;HOLCROFT et al, 1998) and modified atmosphere (SELCUK; ERKAN, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was similar in all gas concentrations, with no interaction effect between treatments and storage period. In minimally processed plants, injuries in the plant tissue caused by cutting the fruits and/or vegetables lead to an increase of respiratory rate and ethylene production, causing a stimulus to the formation of secondary metabolites, which are produced as a plant defense mechanism (ALARCÓN-FLORES et al, 2015;KLUGE et al, 2006), and may increase the functional food value. In addition, the biosynthesis of phenolic compounds may continue after harvest and increase during storage at low temperatures (CONCELLÓN et al, 2007;HOLCROFT et al, 1998) and modified atmosphere (SELCUK; ERKAN, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Their uses in indigenous medicine range from weight reduction to the treatment of many ailments including asthma, allergic rhinitis, nasal catarrh, skin infections, rheumatic diseases and swollen joint pains, gastroesophageal reflux, constipation, dyspepsia [3]. Several studies support the folkloric use of plants in local foods and medicinal preparations; For example, various investigators reported significant analgesic, antiinflammatory, anti-asthmatic, anti-glaucoma, hypoglycemic, hypolipidemic and weight loss effects of eggplants, particularly S. melongena, on test animals and animals human beings [4]. Pharmacological properties have been attributed to the presence of certain chemical substances in plants, such as fibers, ascorbic acid, phenols, anthocyanins, glycoalkaloids and α-chaconine [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, given the lack of comprehensive studies on the eggplant genome, only 775 pathogen recognition genes have been reported in the eggplant, compared to more than 1,000 genes in each of the three other Solanaceae crops (tomato, pepper, and potato) [22], which influences the progress of studies on the evolution of disease resistance in different Solanaceae plants [23]. Eggplants are the richest source of chlorogenic acid (CGA; 5- O -caffeoylquinic acid) [24, 25]. This dietary phenolic acid has been proven to exhibit anti-inflammatory, antimutagenic, and antiproliferative activities; however, the mechanism of CGA formation in the eggplant has not been well elucidated [26, 27].…”
Section: Introductionmentioning
confidence: 99%